2023
DOI: 10.1186/s12889-022-14906-y
|View full text |Cite
|
Sign up to set email alerts
|

When schools were open for in-person teaching during the COVID-19 pandemic - the nordic experience on control measures and transmission in schools during the delta wave

Abstract: Background Extensive measures to control spread of SARS-CoV-2 have led to limited access to education for millions of children and adolescents during the COVID-19 pandemic. Education and access to schools is vital for children and adolescents’ learning, health, and wellbeing. Based on high vaccine uptake and low incidence levels, the Nordic countries (Denmark, Finland, Iceland, Norway and Sweden) decided to start the academic year 2021/22 with schools open for in-person teaching and moderate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…National overviews on the occurrence of cases and clusters in schools, including testing rates and vaccination coverage, are, to our knowledge, still scarce in the literature. However, our findings are consistent with data from Norway where more clusters occurred in primary schools than in secondary schools [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…National overviews on the occurrence of cases and clusters in schools, including testing rates and vaccination coverage, are, to our knowledge, still scarce in the literature. However, our findings are consistent with data from Norway where more clusters occurred in primary schools than in secondary schools [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…This does not seem surprising considering that young children were susceptible throughout the majority of the study period as vaccination roll-out for children 5 to 11 years did not begin until the end of November [ 23 ]. A similar trend was seen in the incidence rates in the general Danish population, where the age group 6 to 11 years had the highest incidence among the age groups during the study period [ 24 , 25 ]. National overviews on the occurrence of cases and clusters in schools, including testing rates and vaccination coverage, are, to our knowledge, still scarce in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have described a shift to increased cases among children and adolescents with the Delta variant but the relative contribution of previous immunity and relaxation of restrictions such as school closures vs intrinsic characteristics of the VOC remains unclear [ 13 , 14 ]. Data on the age distribution of individuals infected with the Beta variant are more limited because of its limited geographic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described a shift to increased cases among children and adolescents with the Delta variant but the relative contribution of previous immunity and relaxation of restrictions such as school closures vs intrinsic characteristics of the VOC remains unclear. 13,14 Data are more limited on the Beta variant but a South African surveillance study found an increased incidence of diagnosed cases among individuals aged 1-18 years with the Beta variant compared to ancestral. 15 The same study also found increased incidence with Delta compared to Beta in this age group.…”
Section: Discussionmentioning
confidence: 99%